1984
DOI: 10.1152/ajpcell.1984.246.5.c391
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cl- -HCO3(-) exchange during recovery from intracellular acidosis in cardiac Purkinje strands

Abstract: The possible role of a Cl- -HCO3(-) exchange mechanism in the recovery from intracellular acidosis of isolated cardiac Purkinje strands was investigated. Intracellular pH (pHi) was measured using double-barreled pH-sensitive microelectrodes. Acidifications were produced by withdrawing 20 meq NH+4 from the superfusate. Experiments were performed in normal CO2-HCO3(-)-buffered, in HCO3(-)free, and in Cl-free solutions and also in the presence of 4-acetamido-4'-isothiocyanostilbene-2,2'-disulfonic acid (SITS), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 25 publications
6
25
0
Order By: Relevance
“…Physiological importance of the Na+-HCO3-symport It is puzzling that, despite the clear evidence presented here, HCO3--activated acid-equivalent extrusion has not hitherto been observed in mammalian cardiac muscle (Vaughan-Jones, 1982;Vanheel et al 1984;Weissberg et al 1989). The reason for this is not known.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Physiological importance of the Na+-HCO3-symport It is puzzling that, despite the clear evidence presented here, HCO3--activated acid-equivalent extrusion has not hitherto been observed in mammalian cardiac muscle (Vaughan-Jones, 1982;Vanheel et al 1984;Weissberg et al 1989). The reason for this is not known.…”
mentioning
confidence: 58%
“…Deitmer & Ellis, 1980;Kaila & Vaughan-Jones, 1987). Nevertheless, some studies looked specifically for the existence of HC03--dependent acid extrusion in cardiac tissue and failed to detect it (Vaughan-Jones, 1982;Vanheel, de Hemptinne & Leusen, 1984;Piwnica-Worms, Jacob, Horres & Lieberman, 1985;Weissberg et al 1989). More recently, Liu et al (1990) have described a sodium-and bicarbonate-dependent acid extrusion mechanism in the chick heart but they attributed this to a Na+-dependent Cl--HCO3-exchanger.…”
Section: Discussionmentioning
confidence: 99%
“…Vanheel, de Hemptinne & Leusen, 1984). This may explain the observation that GABA had a slight depolarizing action in the nominal absence of HCO3-, an effect which was potentiated in the absence of extra-and intracellular Cl-.…”
Section: Gaba-gated Bicarbonate Conductancementioning
confidence: 95%
“…Therefore, interpretations of the present results entirely rest on the assumption that SITS and DIDS at the concentrations employed in the present experiments mainly act as a blocker for Cl--HCO3-exchange; If this is the case, then the present findings of SITS and DIDS-induced attenuation of the development of intracellular acidosis during the initial phase of simulated ischemia could be explained as a consequence of the blockade of the CI--HCO3-exchange. This idea might appear surprising at first because it has been believed that the hypoxic acidification is primarily due to the production of lactic acid (2,4,51), and Cl--HCO3-exchange plays a role in the recovery from intracellular alkalinization, while the exchanger activity is decreased at acid pHi (15,18,21,23). Moreover, in cultured chick heart cells, a Nat-dependent Cl--HCO3-exchange regulates pHi after cell acidification and can cause cell alkalinization (17).…”
Section: Actions Of Sits and Dids On Action Potentials During Ischemiamentioning
confidence: 99%
“…Most studies suggest that the recovery of pH; from acidosis is mediated by several sarcolemmal ion transports including Na+-H+ exchange, Na+-HCO3-cotransport, and Na+-dependent Cl--HCO3-exchange, but the recovery from alkalosis is mediated by Na+-independent Cl--HCO3-exchange. In Purkinje fiber, Vanheel et al (21) showed that acid extrusion was not impaired when the [Cl-];-[HCO3-]o exchange was blocked, whereas other investigators suggested that the Na+-dependent CI--HCO3-exchange plays a significant role in pH, regulation in isolated chick heart cells (17) and in quiescent Purkinje fibers (22,23). More recently, the existence of HC03-dependent pH, regulation (Na+-HCO3 symport) in the guinea pig ventricular myocyte has been also proposed (24).…”
mentioning
confidence: 99%